2016
DOI: 10.1021/acs.macromol.6b02033
|View full text |Cite
|
Sign up to set email alerts
|

Design of Graft Block Polymer Thermoplastics

Abstract: Graft block polymers are defined by several architectural parameters, including backbone flexibility, graft density, backbone length, side-chain composition, and sidechain length. In this work we probe the impacts of each of these parameters on the phase behavior, rheological properties, and mechanical performance of these materials. Specifically, we examine two sets of materials prepared from backbones of different inherent flexibility. One set was prepared from poly[(n-butyl acrylate)-co-(2-hydroxyethyl acry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
84
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(87 citation statements)
references
References 48 publications
2
84
0
Order By: Relevance
“…[13][14][15][16] Recent studies have harnessed these properties in a wide variety of applications in photonics, [17][18][19] drug delivery, [20][21][22] transport, [23][24] and thermoplastics. [25][26] Continued progress in synthetic command over polymer architecture enables further studies of structure-property relationships and inspires new potential applications.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16] Recent studies have harnessed these properties in a wide variety of applications in photonics, [17][18][19] drug delivery, [20][21][22] transport, [23][24] and thermoplastics. [25][26] Continued progress in synthetic command over polymer architecture enables further studies of structure-property relationships and inspires new potential applications.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that the value of Young's modulus decreased when the higher amount of MYR was present in the resin. It could be explained by the formation of MYR soft and flexible chains and by lower crosslinking density in such cases leading to the loss of polymer stiffness …”
Section: Resultsmentioning
confidence: 99%
“…Differential scanning calorimetry (DSC) was used to reveal the phase segregation in obtained materials, as shown in Figure A. It is evident that all block polymers with varying compositions displayed two distinct glass transition temperatures ( T g, M and T g, B y T z ) . The T g values before and after metal coordination are also listed in Table .…”
Section: Resultsmentioning
confidence: 99%
“…In the current plastic industry, the few commodity homopolymers and random copolymers still occupy the majority of market share, but block polymers provide a remarkably large space for tailoring the microstructure and consequent material properties . It is benefited from the unique microphase separation and a wide window of structural parameters for the molecular architecture . In this paper, we combined the merits of block polymers and reversible metal–thioether coordination to build a new type of smart thermoplastic materials ( Scheme ).…”
Section: Introductionmentioning
confidence: 99%